2009
DOI: 10.1080/15374410903258967
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Drinking Motive Questionnaire Revised Short Form (DMQ–R SF)

Abstract: A short form of the Drinking Motive Questionnaire Revised (DMQ-R; Cooper, 1994) was developed, using different item selection strategies based on a national representative sample of 5,617 12- to 18-year-old students in Switzerland. To confirm the concurrent validity of the short-form questionnaire, or DMQ-R SF, data from a second national sample of 2,398 12- to 17-year-old students were analyzed by means of structural equation modeling. The results confirmed the four-dimensional factor structure of the DMQ-R S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
248
3
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 258 publications
(301 citation statements)
references
References 33 publications
24
248
3
26
Order By: Relevance
“…With an overall CFI of at least .95 and an SRMR of .034 and consistent with previous research (Kuntsche and Kuntsche, 2009;Mazzardis et al, 2010;Németh et al, 2011aNémeth et al, , 2011b, the results showed a good model fi t of the DMQ-R SF across age groups. It was only in some countries (e.g., Estonia and Portugal) that the model fi t was somewhat poorer.…”
Section: Factor Structuresupporting
confidence: 76%
See 3 more Smart Citations
“…With an overall CFI of at least .95 and an SRMR of .034 and consistent with previous research (Kuntsche and Kuntsche, 2009;Mazzardis et al, 2010;Németh et al, 2011aNémeth et al, , 2011b, the results showed a good model fi t of the DMQ-R SF across age groups. It was only in some countries (e.g., Estonia and Portugal) that the model fi t was somewhat poorer.…”
Section: Factor Structuresupporting
confidence: 76%
“…Only in the past few years have studies in a range of more diverse countries such as Great Britain (Atwell et al, 2011;Bruce et al, 2012), Germany (Wurdak et al, 2010), Hungary (Németh et al, 2011a;Urbán et al, 2008), Italy (Graziano et al, 2010;Mazzardis et al, 2010), the Netherlands (Crutzen and Kuntsche, 2013;SchellemanOffermans et al, 2011), Spain (Mezquita et al, 2011;Németh et al, 2011b), and Sweden (Comasco et al, 2010) investigated the structure of drinking motives and/or their links to alcohol-related outcomes. The evidence from these studies and from previous research is fairly consistent in that adolescents reported that they drank most often for social motives, followed by enhancement, coping, and conformity motives in that order (Cooper, 1994;Kuntsche and Kuntsche, 2009;Kuntsche et al, 2008).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…33 Participants were asked to indicate their frequency of drinking for each of the 12 specific reasons in the last 12 months using a five-point Likert scale ranging from (almost) never (coded 1) to (almost) always (5). The mean score per motive dimension was used (Cronbach's α varying between 0.82 and 0.87).…”
Section: Methodsmentioning
confidence: 99%